(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the impact of different restorative techniques to treat deep caries lesions of primary molars on children’s self-reported discomfort. A randomized clinical trial with two parallel arms (1:1) was conducted in São Paulo, Brazil. 4-8 years-old children with at least one occlusal or occlusoproximal deep caries lesion in primary molars were selected. Molars were randomly allocated into two groups: (1) restoration performed with calcium hydroxide cement followed by high-viscosity Glass Ionomer Cement (CHC+HVGIC), and (2) HVGIC restoration. Immediately after the intervention, children reported the experienced discomfort during restoration to an external examiner using a Wong-Baker face-scale. Children’s self-reported discomfort was analyzed using Poisson regression comparing both groups and assessing other variables’ influence (α=5%). One hundred and eight children fulfilled the eligibility criteria and were randomized in the two groups (n=54). Most of the children who received CHC+HVGIC restorations reported none or minimal discomfort (83.3%). Similar scores (92.6%) were reported for those treated with HVGIC (p=0.758). The mean reported discomfort in children with CHC+HVGIC restorations was 0.37(1.01), and 0.41(1.01) for those with HVGIC restorations. Children’s self-reported discomfort was associated with age, sex, children’s cooperation, and intervention duration. We can conclude that CHC+HVGIC or HVGIC restorations result in none or minimal discomfort in the management of deep caries lesions, being considered a reliable option.